2002
DOI: 10.1212/01.wnl.0000038347.48137.67
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence among HIV+ adults

Abstract: HIV-infected adults with significant neurocognitive compromise are at risk for poor medication adherence, particularly if they have been prescribed a complex dosing regimen. As such, simpler dosing schedules for more cognitively impaired patients might improve adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
317
0
16

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(357 citation statements)
references
References 46 publications
24
317
0
16
Order By: Relevance
“…This study supports and extends previous reports regarding the everyday life significance of NP impairments associated with HIV infection (Albert et al, 1995;Heaton et al, 1996;Hinkin et al, 2002;Marcotte et al, 1999;Stern et al, 1991). It is the largest such study to date and the most comprehensive in its coverage of both performance-based measures of IADLs and manifest measures of daily functioning outside of the laboratory.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study supports and extends previous reports regarding the everyday life significance of NP impairments associated with HIV infection (Albert et al, 1995;Heaton et al, 1996;Hinkin et al, 2002;Marcotte et al, 1999;Stern et al, 1991). It is the largest such study to date and the most comprehensive in its coverage of both performance-based measures of IADLs and manifest measures of daily functioning outside of the laboratory.…”
Section: Discussionsupporting
confidence: 89%
“…However, a limitation of the current study is that it did not include a measure of participants' accuracy in following their own antiretroviral medication regimens. For example, Hinkin et al (2002) have used electronic monitoring technology (MEMS caps) to track medication use in HIV infected adults, and found that those who were NP-impaired evidenced worse adherence to their prescribed regimens. Future research with laboratory based medication management tasks should seek to validate them using MEMS caps or other objective methods of assessing adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that HIV-associated neurocognitive disturbances, which are common and more prominent as the disease advances, might be responsible for some of the cases of poor medication adherence. Other studies have reported a significantly greater risk of poor adherence to HAART in HIVinfected persons with neurocognitive impairment (Hinkin et al 2002). Depression has been associated with immune suppression and other health outcomes in studies of individual with and without chronic disease (; Herbert & Cohen 1993;Rover et al, 1991).…”
Section: Consequences Of Neuropsychiatric Problems In Patients With Hmentioning
confidence: 97%
“…A presença do HIV-1 no SNC pode ser a principal responsável pelas manifestações neuropsicológicas e por alterações na qualidade de vida do indivíduo (Hinkin et al, 2002;Mehan & Brush, 2001;Odiase, Ogurin & Ogunniyi, 2007). Estas ocorrem como distúrbios de diversos graus nas áreas motora, comportamental e cognitiva (Vitiello et al, 2007 Nos estágios precoces do complexo demencial da AIDS, os resultados de exames neurológicos podem ser normais (Cohen, Perlstein & Braver, 1997;MacArthur et al, 2003).…”
unclassified